Social Changes in the community After 24-Hour Electricity in Temajuk Village, Paloh District, Sambas Regency - Andini, Meri; Mukhlis, Mukhlis; Yulianti, Yulianti; Marini, Marini; Hasanah, Hasanah; Paramitha, Rizqi Ratna (Pancasila International Journal of Applied Social Science, 2024)
This study aims to find out and describe the social changes in the community in Temajuk Village after the existence of 24-hour electricity from the social, economic, and cultural aspects. The theory used in this study is the Theory of the Dimension of Social Change (Himes and Moore). The method used in this study is qualitative research with a descriptive approach. The data collection technique uses observation, interview, and documentation techniques. The informants of this research were determined using the purposive sampling technique according to the criteria that had been determined, namely inn owners, homemakers who sell online, the general public, village heads, village officials, and PLN technical supervisors. The data analysis technique used is an analysis model from Miles and Huberman that goes through three stages: data reduction, data presentation, and conclusion. The results of this study are, first, the structural dimension related to the economic aspects of the community. There is a change in the role/emergence of a new role for homemakers to become online traders and changes in access to the activities of inn owners by utilizing 24-hour electricity facilitated by PT PLN to increase income. Both dimensions relate to cultural changes in children's language and habits. The use of language from social media began to grow, and traditional game habits began to be abandoned. The three interactional dimensions are related to social aspects, namely community interaction, which is the reduction of interaction intimacy in the family and the closer interaction between communities in Temajuk Village.